Efficacy of Various Wavelengths of Monochromatic Light Emitting Diode Illumination on Growth and Performance of Broiler Chickens - Leigh, M.B.; McFadden, T.B.; Schumacher, L.; Firman , J.D. (International Journal of Poultry Science, 2017)
Background and Objective: Lighting is a powerful exogenous stimulus that controls many physiological and behavioral processes in the broiler chicken. Traditionally, incandescent lighting has been used as the standard throughout the broiler industry. New technology has recently become available including LED lighting. Previous studies have shown possible advantages in broiler performance under lighting by various colored LED lights. These reports are ambiguous and it is still quite unclear as to which lighting source would be most advantageous. The objective of this study was to evaluate the effects of various wavelengths of monochromatic light emitting diode illumination on growth and performance of broiler chickens raised in a commercial-style setting. Methodology: The experiment was designed as a randomized complete block with 4 treatments applied to each of 12 replicate pens of 30 birds/pen. Broilers were reared under standard white LED, green LED, blue LED and red LED lighting from 0-49 days of age and were monitored at days 17, 35 and 49 for individual bird body weight gain, feed intake and feed conversion ratio. Results: There were no statistical differences between treatment groups for daily and overall body weight gain, daily and overall feed intake, feed conversion ratio and percent mortality, with the exception of slightly lower body weight (BW) at 35 days in the green LED treatment. Overall, there were no statistical differences in performance for the trial. At day 50, birds were processed for parts yield. No statistical differences between treatments were observed for carcass yield, fat pad, pectoralis major, total pectoralis, thigh, wing or leg as a percentage of cold carcass. However, pectoralis minor and wing yield showed minor differences. Conclusion: Broiler performance was similar under all wavelengths of LED lights compared in this study.